COMPUTATIONAL SIMULATION OF ENGINE COOLING SYSTEM PERFORMANCE OF A COMMERCIAL CAR - Chen , Tien Hao (IRC, 2020)
Engine cooling system one of the important parts for a vehicle which it responsible is to maintain the engine temperature to work at an optimum temperature. Heat transfer coefficient of engine coolant is an important aspect in the performance of engine cooling system. This paper analyses on the simulation of coolant performance in an engine cooling system by using different concentration (0.1%, 0.25% and 0.5%) MWCNT nanoparticles in water/ethylene glycol based multi-walled carbon nanotubes (MWCNT) and lastly comparison between the base coolant which is ethylene glycol + water. As many researchers had proved that nanofluid’s heat transfer properties had improved compared to base coolant